Review on textbook «Medical microbiology, virology and immunology». Textbook for the students of higher medical educational establishments / edited by V.P. Shyrobokov. – Vinnytsa: Nova kniha, 2011. – 952 p. with ill., and its edition in Russian «Medical m - A. I. Vinnikov (Medičnì Perspektivi)
Review on textbook «Medical microbiology, virology and immunology». Textbook for the students of higher medical educational establishments / edited by V.P. Shyrobokov. – Vinnytsa: Nova kniha, 2011. – 952 p. with ill., and its edition in Russian «Medical microbiology, virology and immunology. – 2015.»